2015
DOI: 10.18410/jebmh/2015/18
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Intrathecal Dexmedetomidine and Fentanyl as Adjuvants to Bupivacaine for Lower Abdominal Surgeries

Abstract: Various adjuvants have been used with local anesthetics in spinal anesthesia to improve the quality of block and to provide prolonged postoperative analgesia. Dexmedetomidine, the new highly selective α2-agonist drug, is now being used as a neuraxial adjuvant. AIM: The aim of this study was to evaluate the onset and duration of sensory and motor block, hemodynamic effect, postoperative analgesia, and adverse effects of dexmedetomidine or fentanyl given intrathecally with hyperbaric 0.5% bupivacaine. METHODOLOG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 20 publications
4
1
1
Order By: Relevance
“…Similar results were also noted by Kishore et al, [19] Mehendru V et al, [18] Gupta R et al [21] Motor block onset time to modified Bromage 3 was also observed but no statistically significant differences were found. Similar findings were noted by Gupta et al, Mehendru V et al [18] and Kishore et al [19] Heart rate (HR), mean arterial blood pressure (MAP) at baseline, just after dural puncture, at 3 min intervals till first 15min, then at 5min intervals till 90 min were compared. Though there was theoretical possibility of lowering of HR [22] , difference of HR was not statistically significant at all the above intervals.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Similar results were also noted by Kishore et al, [19] Mehendru V et al, [18] Gupta R et al [21] Motor block onset time to modified Bromage 3 was also observed but no statistically significant differences were found. Similar findings were noted by Gupta et al, Mehendru V et al [18] and Kishore et al [19] Heart rate (HR), mean arterial blood pressure (MAP) at baseline, just after dural puncture, at 3 min intervals till first 15min, then at 5min intervals till 90 min were compared. Though there was theoretical possibility of lowering of HR [22] , difference of HR was not statistically significant at all the above intervals.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly for MAP, no statistical significant difference was observed in our study between these two groups in above mentioned intervals. Similar observation was also noted by Mahendru V et al, [18] Kishore et al, [19] and Gupta R et al [21] Two segment sensory regression from highest sensory block level, sensory block regression to S1 level and motor block regression to modified Bromage 0 was compared between this two groups. The differences for all this three parameters were very much statistically significant (P<0.0001).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations